Refleksi Keterlaksanaan PPL PPG Prajabatan Berbasis Lesson Study di SMP 4 Padang - Khairi, Rahmad; Nofrion, Nofrion (Lembaga Yasin AlSys, 2024)
This research aims to analyze the reflection of the implementation of Lesson Study-based Pre-service PPG PPL in SMP 4 Padang. Using descriptive qualitative research methods, data were collected through interviews, observations, and documentation. The results showed that the planning of PPL PPG was carried out collaboratively with a focus on preparing learning tools such as ATP and teaching modules that were aligned with the independent curriculum. Learning implementation was effective with the use of problem-based learning methods and interactive media, although there were challenges in classroom management. The presence of many teachers during the Lesson Study did not disrupt the students' learning process, and even increased their enthusiasm for learning. Reflection was conducted after the lesson to evaluate the effectiveness of the strategies used and the level of student engagement. The problem-based learning approach proved to be able to increase students' participation and understanding, but there were still challenges in keeping the class conducive. This research concludes that the Lesson Study-based Pre-Service PPG PPL at SMP 4 Padang has run well, providing benefits for improving the quality of learning and developing prospective teachers' competencies, although there are still some aspects that need to be improved.